(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This research aimed to develop an intelligent system for ranking the cultural wisdom and artistic heritage of universities in Thailand under the initiative “U-Culture Thailand Ranking.” The study emphasized synthesizing cultural wisdom data related to the core missions of universities, as well as defining key components, indicators, weightings, and explicit evaluation criteria. A qualitative research design was employed in combination with expert and stakeholder validation, alongside the development of an online application following the System Development Life Cycle (SDLC). The findings revealed that cultural wisdom in Thai universities encompasses five major dimensions: (1) cultural infrastructure, (2) curricula and cultural integration, (3) cultural research and innovation, (4) management and budgeting, and (5) community engagement and social recognition. The developed indicators demonstrated content validity, appropriateness, and practical applicability. As an innovation, the indicators enhance transparency, accuracy, and multi-stakeholder participation, thereby contributing to sustainable promotion of cultural wisdom, strengthening of soft power, and elevating the role of Thai universities on the international stage.